2022
DOI: 10.1002/hsr2.746
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative outcomes in robotic gastric resection compared with laparoscopic gastric resection in gastric cancer: A meta‐analysis and systemic review

Abstract: Background: Robotic gastrectomy is a commonly used procedure for early gastric cancer and it also overcomes the limitation of laparoscopic. However, the complications of robotic gastrectomy (RG) still need to be assessed. Our study was designed to compare postoperative complications of RG with laparoscopic gastrectomy (LG). Materials and Methods:A meta-analysis and systemic review were prospectively collected using the PubMed, Cochrane Library, and MEDLINE database of published studies by comparing the RG and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 51 publications
(145 reference statements)
1
9
0
Order By: Relevance
“…Similar outcomes were observed in the same study regarding CD III grade or higher, with the robotic approach having a complication rate of 5.3%, whereas the laparoscopic approach reached 19.7%. The results of Ojima et al [3] agree with the results from Loureiro et al [34], Ali et al [33], and Guerrini et al [24], which observed that the robotic approach decreased the surgical complication rate by 32%, 40%, and 34%, respectively, for CD III grades or higher.…”
Section: Overall and Surgical Complication Ratessupporting
confidence: 80%
See 4 more Smart Citations
“…Similar outcomes were observed in the same study regarding CD III grade or higher, with the robotic approach having a complication rate of 5.3%, whereas the laparoscopic approach reached 19.7%. The results of Ojima et al [3] agree with the results from Loureiro et al [34], Ali et al [33], and Guerrini et al [24], which observed that the robotic approach decreased the surgical complication rate by 32%, 40%, and 34%, respectively, for CD III grades or higher.…”
Section: Overall and Surgical Complication Ratessupporting
confidence: 80%
“…For instance, Ojima et al concluded that the conversion for the robotic approach was 3.4% versus 1.6% for the laparoscopic approach [3]. However, no statistically significant differences were observed in all the studies [3,5,7,10,11,15,22,24,26,29,[32][33][34]…”
Section: Conversion To Open Surgerymentioning
confidence: 99%
See 3 more Smart Citations